Uncertainty Management Among Older Adults with Heart Failure: Responses to Receiving Implanted Device Data using a Fictitious Scenario Interview Method. Issue 1 (September 2019) - Daley, Carly; Cornet, Victor; Patekar, Gauri; Kosarabe, Swapnil; Bolchini, Davide; Toscos, Tammy; Mirro, Michael; Wagner, Shauna; Martin, Elizabeth; Ghahari, Romisa Rohani; Ahmed, Ryan; Miller, Amy; et al.
Heart failure (HF) is a complex chronic illness that affects the older adult population, requiring medical therapy and day-to-day management to prevent worsening and exacerbation. Patients with HF are often treated with cardiac implanted electronic devices (CIEDs) which capture diagnostic and predictive parameters for HF. In this work we explore how patients would respond to receiving data from an implanted device, using a fictitious scenario interview method with 24 older adults with HF. We applied an uncertainty management lens to better understand how patients face uncertain outcomes and integrate novel data into their decision making. The findings provide insight into how patients would engage and respond to a technology which provides an indicator of their HF status from an implanted device.